An Eocene orthocone from Antarctica shows convergent evolution of internally shelled cephalopods. - Larisa A Doguzhaeva; Stefan Bengtson; Marcelo A Reguero; Thomas Mörs (PLoS ONE, 2017)
BACKGROUND:The Subclass Coleoidea (Class Cephalopoda) accommodates the diverse present-day internally shelled cephalopod mollusks (Spirula, Sepia and octopuses, squids, Vampyroteuthis) and also extinct internally shelled cephalopods. Recent Spirula represents a unique coleoid retaining shell structures, a narrow marginal siphuncle and globular protoconch that signify the ancestry of the subclass Coleoidea from the Paleozoic subclass Bactritoidea. This hypothesis has been recently supported by newly recorded diverse bactritoid-like coleoids from the Carboniferous of the USA, but prior to this study no fossil cephalopod indicative of an endochochleate branch with an origin independent from subclass Bactritoidea has been reported. METHODOLOGY/PRINCIPAL FINDINGS:Two orthoconic conchs were recovered from the Early Eocene of Seymour Island at the tip of the Antarctic Peninsula, Antarctica. They have loosely mineralized organic-rich chitin-compatible microlaminated shell walls and broadly expanded central siphuncles. The morphological, ultrustructural and chemical data were determined and characterized through comparisons with extant and extinct taxa using Scanning Electron Microscopy/Energy Dispersive Spectrometry (SEM/EDS). CONCLUSIONS/SIGNIFICANCE:Our study presents the first evidence for an evolutionary lineage of internally shelled cephalopods with independent origin from Bactritoidea/Coleoidea, indicating convergent evolution with the subclass Coleoidea. A new subclass Paracoleoidea Doguzhaeva n. subcl. is established for accommodation of orthoconic cephalopods with the internal shell associated with a broadly expanded central siphuncle. Antarcticerida Doguzhaeva n. ord., Antarcticeratidae Doguzhaeva n. fam., Antarcticeras nordenskjoeldi Doguzhaeva n. gen., n. sp. are described within the subclass Paracoleoidea. The analysis of organic-rich shell preservation of A. nordenskjoeldi by use of SEM/EDS techniques revealed fossilization of hyposeptal cameral soft tissues. This suggests that a depositional environment favoring soft-tissue preservation was the factor enabling conservation of the weakly mineralized shell of A. nordenskjoeldi.